Impact of diet on vitamin D status in a selected population of pregnant mothers in Sri Lanka - Anusha Kaneshapillai; Guwani Liyanage; Usha Hettiaratchi (Universitas Muhammadiyah Ponorogo, 2018)
Context: Results of various studies have shown severe vitamin D deficiency in the Indian subcontinent in all age groups and insufficiency in populations of South-East and East Asia. There are no data available in Sri Lanka on vitamin D status in pregnant mothers. Vitamin D supplements are not provided routinely in state sector clinics. Institute of Medicine of the National Academy of Sciences in the USA recommends safe upper limit of dietary vitamin D as 4000 IU.Aims: Thus, our aim of this study was to assess vitamin D status and adequacy of vitamin D intake through diet among pregnant mothers.Settings and Design: This is a secondary analysis of data of a prospective cohort study.Methods and Material: 89 pregnant mothers in their 3rd trimester were recruited. Food frequency questionnaire based on 7-day estimated food record method was used. Analysis of blood sample was done for vitamin D, parathyroid hormone (PTH), calcium, inorganic phosphorous and alkaline phophatase levels.Statistical analysis used: Spearman’s correlation and independent sample t-test were performed.Results: We found that 12.4%, 50.6% and 37.1% were vitamin D deficient, insufficient and sufficient respectively. 25(OH)D and PTH showed a significant negative correlation (r=0.296; P0.01). Yet, serum PTH level was above the cut-off only among 4.5%. Further, only 13.5% subjects had high ALP (240 IU/L). Average daily intake of vitamin D through diet was 1289.4 ± 1225.6 IU/day (range 56 IU- 5400 IU). Significant Main source of vitamin D was fortified milk powder and small fish.Conclusions: High rate of vitamin D insufficiency/deficiency was observed and this novel finding in our cohort suggests investigating vitamin D status in pregnant mothers at a national level. Vitamin D intake through diet was not adequate in our study sample. Further, rigorous trails are needed to evaluate the requirement for supplementation to optimise the bone metabolism during pregnancy in Sri Lanka.